The Relationship Between Perception of Halal Certification and Purchase Decision of Contemporary Drinks among Students of Jenderal Soedirman University - Junita, Sukma; Nuraeni, Indah; Munasib, Munasib; Proverawati, Atikah; Ramadhan, Gumintang Ratna (Institute of Research and Public Service Universitas Jenderal Soedirman, 2025)
The development of the food industry in Indonesia has given rise to various kinds of innovative and popular contemporary foods and beverages. Although contemporary drinks are currently popular with consumers in Indonesia, many contemporary drinks do not have halal certification. Muslim consumers must be aware of the halalness of the ingredients and the manufacturing process. This study aims to determine the relationship between the perception of halal certification and the decision to purchase contemporary drinks among students of Jenderal Soedirman University. This study is an explanatory research type with a cross-sectional design. A sample of 106 students of Jenderal Soedirman University was taken using a purposive sampling technique. Data were analyzed using the Spearman Rank test. The results of the study showed that there was a significant relationship between the perception of halal certification and the decision to purchase contemporary drinks among students of Jenderal Soedirman University with the strength of the relationship between variables being quite strong and in the same direction (p = 0.000, correlation coefficient = 0.583).